Inflammation, telomere length, and grip strength: a 10-year longitudinal study. - Baylis, D; Ntani, G; Edwards, M; Syddall, H; Bartlett, D; Dennison, E; Martin-Ruiz, C; von Zglinicki, T; Kuh, D; Lord, J; Aihie Sayer, A; Cooper, C (2014)
Telomere attrition has been associated with age-related diseases, although causality is unclear and controversial; low-grade systemic inflammation (inflammaging) has also been implicated in age-related pathogenesis. Unpicking the relationship between aging, telomere length (TL), and inflammaging is hence essential to the understanding of aging and management of age-related diseases. This longitudinal study explored whether telomere attrition is a cause or consequence of aging and whether inflammaging explains some of the associations between TL and one marker of aging, grip strength. We studied 253 Hertfordshire Ageing Study participants at baseline and 10-year follow-up (mean age at baseline 67.1 years). Participants completed a health questionnaire and had blood samples collected for immune-endocrine and telomere analysis at both time points. Physical aging was characterized at follow-up using grip strength. Faster telomere attrition was associated with lower grip strength at follow-up (β = 0.98, p = 0.035). This association was completely attenuated when adjusted for inflammaging burden (p = 0.86) over the same period. Similarly, greater inflammaging burden was associated with lower grip strength at follow-up (e.g., interleukin [IL]-1β: β = -2.18, p = 0.001). However, these associations were maintained when adjusted for telomere attrition (IL-1β, p = 0.006). We present evidence that inflammaging may be driving telomere attrition and in part explains the associations that have previously been reported between TL and grip strength. Thus, biomarkers of physical aging, such as inflammaging, may require greater exploration. Further work is now indicated.